Two lands, one poet the reflections of Stephan G. Stephansson through poetry - Stephan Guðmundsson Stephansson 1853-1927 (Hin kindin, 2019)
A marvelous bilingual edition of the poetry of Icelandic/ Canadian author and poet, Stephan G. Stephansson (1853 - 1927). His given name was Stefán Guðmundur Guðmundsson and born in Skagafjörður, Iceland but emigrated to Wisconsin, United States in 1873, at age 19. In 1889 he moved to Markerville, Red Deer County, Alberta, Canada. Introduction written by Jón Atli Benediktsson, the rector of the University of Iceland.